Determination of Anther Culture Performance of Some Pepper (Capsicum annuum L.) Genotypes - Didem ATASOY; Gökhan BAKTEMUR; Hatıra TAŞKIN (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
In this study, anther culture performances of 23 pepper genotypes belonging different types were determined. In disinfection of flower buds, the buds were first kept in 70% ethyl alcohol for 30 seconds and then were waited in 15% sodium hypochlorite solution for 10 minutes. The anthers were cultured in Murashige and Skoog (MS) nutrient medium containing 30 g L-1 sucrose, 2.5 g L-1 activated charcoal, 15 mg L-1 silver nitrate (AgNO3), 4 mg L-1 1-Naphthaleneacetic acid (NAA), 0.5 mg L-1 6-Benzylaminopurine (BAP) and 6.5 g L-1 agar in the first stage. The anthers were then transferred to MS medium including 30 g L-1 sucrose and 6.5 g L-1 agar and without growth regulators. The embryos obtained were taken to the same nutrient medium (second one). The anthers were cultured at +35ºC and in dark conditions for 2 days as pre-treatment. When the results of the study were evaluated, average embryo number per hundred anthers according to the genotypes ranged from 0.83 to 44.44. The highest ratio was observed in the genotype FT-509 and it was followed by the genotypes FT-508 (23.61 embryos/100 anthers), FT-1181 (23.37 embryos/100 anthers) and FT-905 (22.89 embryos/100 anthers). The genotype FT-1178 showed the lowest performance with 0.83 embryos/100 anthers. All of the embryos developed could transform into plants. Therefore, the average embryo number forming plant per 100 anthers was the same with average embryo number per hundred anthers. The highest average plant number was observed in the genotype FT-508 with 20 plants and it was followed by the genotypes FT-509 (17.5 plants), FT-1181 (16 plants), FT-905 (12 plants), FT-263 (10.5 plants) and FT-507 (8.25 plants). The lowest number of plant was recorded in the genotype FT-1178 with 0.5 plant.